Insights into leadership practices in South African Higher Education - Beverly G. Venter; Marieta du Plessis; Marius W. Stander (SA Journal of Industrial Psychology, 2024)
Orientation: The complexity of higher education highlights leadership’s significance. Effective leadership ensures quality education and institutional survival, with senior academics (specifically, professors and associate professors) greatly influencing reputation and research. Exploring senior academics’ leadership experiences is therefore crucial.